EMBRACING SOCIAL MEDIA TO IMPROVE EFL LEARNERS' ENGLISH SKILL - Dwi Iswahyuni (PROJECT (Professional Journal of English Education), 2021)
Regarding the importance of exploring the use of social media to enhance English skill, this study investigated the use of social media to improve English skill of EFL learners especially non-English college students. The objective of this study was to find out in what ways social media can contribute to the improvement of EFL learners’ English skill. The research method employed in this study was descriptive qualitative method. In gaining data, this study used questionnaire and observation. The results showed that almost all respondents took advantage of social media to learn English. Some social media used were YouTube, WhatsApp, Instagram, Facebook, Twitter, TikTok, etc. The respondents revealed that by the use of social media, their reading skill (97.3% of the respondents), their writing skill (94.6% of the respondents), their vocabulary mastery (91.9% of the respondents), their listening skill (89.2% of the respondents), their speaking skill (86.5% of the respondents), their grammar mastery (83.8% of the respondents) could be improved. Based on the findings of the study, it can be inferred that social media can contribute to the improvement of EFL learners’ English skill in many ways including reading skill, writing skill, vocabulary mastery, listening skill, speaking skill, and grammar mastery. Keywords:  EFL Learners, English Skill, Social Media